The Value of Field Trips and Experiential Learning in Social Studies - Abdullah, Saman A.; sharif , Sayfadin I.; Qolamani , Khalid I. Basheer (Polytechnic Journal of Humanities and Social Sciences, 2024)
Abstract— Field trips and experiential learning opportunities have historically been employed as teaching instruments within social studies classrooms. This article aims to analyze the theoretical underpinnings and empirical investigations pertaining to the utilization of field excursions and experiential learning within the context of social studies education. This paper will explore the distinct advantages of field trips in facilitating the connection between classroom instruction and real-world environments. In conclusion, this paper will present suggestions for optimizing the educational efficacy of field trips. Keywords—Field trips, Experiential learning, Social studies, Active learning methodologies and Educational efficacy